2003
DOI: 10.1002/jcla.10094
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of liver function test in patients treated with antipsychotics

Abstract: The prevalence of alterations of liver function tests in patients treated with a wide range of antypsychotics is unknown. The aim of this study was to analyze the effects of antipsychotics on liver function tests in a population of schizophrenic outpatients. Concentrations of AST, ALT, GGT, alkaline phosphatase, albumin, and bilirubin were determined in 54 patients fitting DSM-IV criteria of schizophrenia, and the same number of sex- and age-matched healthy subjects. Assessments included the Clinical Global Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…This finding is consistent with documented studies, as these enzymes are reportedly high during the acute stages of psychosis (14)(15)(16)(17)(18)(19). Statistical results showed that this elevation was not significantly different between the dosing groups (CPZE1 and CPZE2).…”
Section: Discussionsupporting
confidence: 82%
“…This finding is consistent with documented studies, as these enzymes are reportedly high during the acute stages of psychosis (14)(15)(16)(17)(18)(19). Statistical results showed that this elevation was not significantly different between the dosing groups (CPZE1 and CPZE2).…”
Section: Discussionsupporting
confidence: 82%
“…Reddy R et al reported significant decrease in bilirubin levels in first episode schizophrenics. 9 Our findings have fair correlation with the findings of Yao JK et al, Umadevi P and Murugan S, Teresa M et al 14,15,21 Yao JK et al also demonstrated significantly lower plasma bilirubin levels in chronic schizophrenic patients either during haloperidol treatment or in a drug-free condition compared with age-and sex-matched healthy volunteers.…”
supporting
confidence: 83%
“…Such studies could also provide information on important risk factors for CHD, including clinical indicators (e.g., cholesterol levels), obesity, and smoking status, which were not available in our health services encounter data. We also were not able to ascertain whether antipsychotic-induced elevated liver enzymes (Garcia-Unzueta et al, 2003) or other liver disorders such as hepatitis that affect many people with SMI (Essock et al, 2003) influenced the prescribing of statins in our study. Finally, although our findings suggest that a lack of guideline concordant care regarding use of cardioprotective medications may contribute, in part, to the increased cardiovascular morbidity and mortality observed in SMI patients, more work is required to elucidate the direct mechanisms leading to poor health outcomes in this population.…”
Section: Discussionmentioning
confidence: 89%